Soil microbiota: Influence of different land use patterns and soil management factors at Villavicencio Oxisol, East Colombia (2017)
The soil microbiota is a biological indicator. The impact of four different land use patterns: Secondary forest (T1), rice monoculture (T2), pineapple monoculture (T3) and agroforestry system of Theobroma cacao associated with Acacia mangium (T4) at different distances: 0-10 cm (D1), 10-20 cm (D2), 20-30 cm (D3), 30- 40 cm (D4) and 40-50 cm (D5) on counts of Colony Forming Units (CFUs) of fungi, bacteria, actinobacteria were tested in an Oxisol of Villavicencio, Orinoquia, East Colombia. An unrestricted random design was applied. More number of CFUs of soil bacteria, fungi and actinobacteria were recorded in secondary forest (T1) at all the distances from the root surface when compared to the other treatments. However, a similar trend was observed for counts of CFUs of soil fungi and bacteria in secondary forest (T1) at (D4) and (D5) distances from the root surface compared with agroforestry system (T4) at all distances from the root surface (P≤0.05). Meanwhile that there was similarity in number of CFUs of soil actinobacteria between secondary forest (T1) and agroforestry system (T4) at all the distances (P≥0.05). The least count of CFUs of soil microbiota was recorded in pineapple monoculture (T3) at all the distances from the root surface (P≤0.05).